2013
DOI: 10.3390/en6083859
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Screening of Residential Buildings for Energy Audit Purposes: Results of a Field Test

Abstract: Abstract:In the European Union (EU), the building sector is responsible for approximately 40% of total energy consumption. The existing building stock is inefficient and can, and indeed must be retrofitted to address this issue. The practical implementation of the European strategies requires knowledge of the energy performance of existing buildings through energy audit techniques. Application of thermography in the fields of energy are very widespread, since, through such a non-invasive investigation, and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 12 publications
5
81
0
4
Order By: Relevance
“…Weather conditions have proven to be highly problematic when implicating short-term IRT [43][44][45], with effects of rain, solar incidence, and wind, leading to a distortion of data and bias in the results. Lucchi [42] goes on to discuss solutions to these problems can be sought by controlling these factors, in order to reduce the impact on the results; suggestions of limiting IRT measurements to dry days with Buildings 2018, 8, 46 6 of 17 low solar incidence, performing IRT during steady conditions, and the acquisition of compensation terms, are all made [44][45][46] Further studies have also sought to perform IRT under controlled conditions, to eliminate the influence of weather, though on a much smaller scale than for whole buildings [47,48].…”
Section: Infrared Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…Weather conditions have proven to be highly problematic when implicating short-term IRT [43][44][45], with effects of rain, solar incidence, and wind, leading to a distortion of data and bias in the results. Lucchi [42] goes on to discuss solutions to these problems can be sought by controlling these factors, in order to reduce the impact on the results; suggestions of limiting IRT measurements to dry days with Buildings 2018, 8, 46 6 of 17 low solar incidence, performing IRT during steady conditions, and the acquisition of compensation terms, are all made [44][45][46] Further studies have also sought to perform IRT under controlled conditions, to eliminate the influence of weather, though on a much smaller scale than for whole buildings [47,48].…”
Section: Infrared Thermographymentioning
confidence: 99%
“…Lucchi [42] goes on to discuss solutions to these problems can be sought by controlling these factors, in order to reduce the impact on the results; suggestions of limiting IRT measurements to dry days with low solar incidence, performing IRT during steady conditions, and the acquisition of compensation terms, are all made [44][45][46] Internal and external variables can have a significant effect on U-value measurement outcomes [35]. Researchers have found that external variables, such as wind, precipitation, long wave radiation, and solar gain can have a major impact.…”
Section: Infrared Thermographymentioning
confidence: 99%
“…A first group of authors [9,10,11,12,13,14,15] recommends to avoid solar irradiation in general, making no judgement of the impact duration. A second group [6,7,8 ], containing also the European Standards on thermography, gives more precise information on the waiting time after sundown to perform a thermographic survey and mentions that structures with high thermal mass need more attention. A third group [2,3,4,5] of authors distinguishes between guidelines for structures with a different thermal mass.…”
Section: Qualitative Inspectionmentioning
confidence: 99%
“…Insulation defects Air leakage spots ∆Ti-e >10°C during 4h prior to IR [20] ∆Ti-e >1,7°C during 4h prior to IR [20] ∆Ti-e > 10°C [10] ∆Ti-e > 3°C [10] ∆Ti-e > 10°C [21] ∆Ti-e > 5°C [21] ∆Ti-e > 10°C [11] ∆Ti-e > 3/U (min 5°C) during 24h prior to IR [8,16] ∆Ti-e > 15°C during 24h prior to IR [15,22] ∆Ti-e > 10 -15°C [13,23] ∆Ti-e > 5°C during 24h prior to IR [6,7,12] ∆Ti-e > 10°C during 4h prior to IR [2,24] ∆Ti-e > 10°C (>20°C if possible for U-value determination) [19] Wind velocity (m/s)…”
Section: Sky Radiationmentioning
confidence: 99%
See 1 more Smart Citation